Kontraversi tentang Tersihirnya Nabi Muhammad saw. - Zuhdi Dh, Achmad (ISLAMICA: Jurnal Studi Keislaman, 2008)
The prophetic saying (hadith) that speaks of the prophet being influenced by the soothsayer has been a subject of controversy among the Muslims over centuries. Some âulama argue that that hadith is not authentic on the ground that it is not logical and is not in line with the very teaching of the Qurâan, sound reason and the overall tenets of Islam. The Muâtazlites are among those who belong to this group. Among the legalists, there are outstanding âulama who are also against this hadith such as Abu Ishaq al-Istarbadi of Shafiâiyyah, Abu Bakr al-Razi al-Jassas of Hanafiyyah, and Ibn Hazm al-Dhahabi of Zahiriyyah. In addition, Muhammad Abduh and Rashid Ridha are listed among the modern scholars who strongly argue against it. Other group of âulama nonetheless argue that that hadith is sound and authentic both in terms of its chain of narration as well as in terms of its text. Imam al-Bukhari, Imam Muslim and Ibn Qayyim belong to this second group of âulama. How do these two groups of âulama with conflicting views develop their argument on the subject, is the question that this paper is interested in answering.